SISTEMATIK REVIEW EFEKTIVITAS DAN MANFAAT PRENATAL YOGA TERHADAP KELUHAN NYERI PUNGGUNG PADA IBU HAMIL - Mardliyana, Nova Elok (Universitas Muhammadiyah Surabaya, 2023)
Objective: Back pain is one of the discomforts experienced by pregnant women, usually occurring in the lumbosacral area, namely in the size of the waist and pelvis. One way to reduce this discomfort is to do physical activity during pregnancy, including prenatal yoga or pregnancy yoga. Yoga in pregnancy involves particular movements and techniques beneficial for pregnant women, such as relaxation techniques, which can reduce the discomfort arising from body changes during pregnancy. This research aims to determine the effectiveness and benefits of prenatal yoga or pregnancy exercises for back pain in pregnant women. Methods: The research method used is a systematic review. Research sources were obtained from searching scientific articles via the internet with the Google Scholar database from 2012-2023 using PICO